Challenges and Open Issues in Transcatheter Mitral Valve Implantation: Smooth Seas Do Not Make Skillful Sailors - Russo, Giulio; Maisano, Francesco; Massaro, Gianluca; Terlizzese, Giuseppe; Mariano, Enrica; Bonanni, Michela; Matteucci, Andrea; Bezzeccheri, Andrea; Benedetto, Daniela; Chiricolo, Gaetano; Martuscelli, Eugenio; Sangiorgi, Giuseppe Massimo (Frontiers in Cardiovascular Medicine, 2022)
According to European and American guidelines, surgery represents the treatment of choice for MV disease. However, a number of patients are deemed unsuitable for surgery due to prohibitive/high operative risk. In such cases, transcatheter therapies aiming at mitral valve repair represent a valuable alternative and have been recently introduced in the last American guidelines on valvular heart disease. Indeed, percutaneous repair techniques, in particular transcatheter edge-to-edge, have gained large experience and demonstrated to be safe and effective. However, given the complexity and heterogeneity of mitral valve anatomy and pathology, transcatheter mitral valve implantation (TMVI) has grown as a possible alternative to percutaneous MV repair. Current data about TMVI are still limited and come from different settings: valve in native, valve-in-valve, valve-in-ring and valve-in-mitral annular calcification. Preliminary data are promising although several open issues still need to be addressed. This paper provides a comprehensive review of the available devices in the different clinical settings, discussing potentialities, limitations and future directions for TMVI.